Social support among Systemic Lupus Erythematosus (SLE) patient in Malaysia - Azimatun Noor Aizuddin; Mohd Haazik Mohamed; Sangaran Gopal; Hazlina Mohd Miskam; Idayu Badilla Idris (Southeast Asia Psychology Journal, 2023)
This research aims to look at the social support available for the Systemic Lupus Erythematosus (SLE) patient and its relationship with sociodemographic and psychological factors in Universiti Kebangsaan Malaysia Medical Center, Kuala Lumpur, Malaysia. A total of 150 patient with SLE who are seeking treatment have filled the questionnaires distributed and consist of 26 male patients and 126 female patients with a ratio (1:4.8). A cross sectional study using the convenience sampling was conducted where the MSPSS questionnaires (Multidimensional Scale of Perceived Social Support) was used to measure the social support scores while Hospital Anxiety and Depression (HADS) was used to measure the psychological aspect obtained by patient. The social support overall showed a significant relationship only with the monthly income. Family social support were significantly related to ethnicity and income, friends social support seen to have a significant relationship with education and income, where else there is no significant relationship between significant other social support with demographic characteristics of patient with SLE. There result showed that there was a negative strong significant relationship between social support overall, social support from family, social support from friends and social support from significant other with score of anxiety and depression. All the test results showed p<0.000 and r>-0.6. This means that there is a significant relationship between social support, family social support, friend social support and social support of special friend with the occurrence of anxiety and depression experienced by patients with SLE.